RANCANG BANGUN KATEGORI PEMETAAN PADA SISTEM INFORMASI GEOGRAFIS - ROBITOTUL MU'AWANAH; Primaadi Airlangga; Munawarah Munawarah (SAINTEKBU, 2022)
Categories are part of the classification system (group, rank type and so on). In an integrated mapping system, a lot of data and mapping types make it difficult to search for data if you have to select one by one. A search system was created to simplify the search, which also contained categories. Mapping Categories can make it easier to search for mappings according to their respective categories. Therefore the design of mapping categories in this geographic information system makes how to enter categories in mapping, which can then be displayed in adding category names so that data on category names can be displayed in tabular form in category searches. In searching for categories, users can not only fill in one category in the search column but in more than one category. However, the name entered in the search column must match the category name; if it does not, the category name will not be displayed in the category names table. This method can help users find mappings that are similar or related to what they need. Please adjust the image so that it reads well to the reader